A taxonomic correction after 140 years. (24th November 2016) - Dutta, Rakhi; Bardhan, Subhendu
Abstract: Waagen (1875) was the first who dealt with the Jurassic ammonites of Kutch based on detailed taxonomic work. In his monograph, he described among many species Perisphinctes spirorbis Neumayr, 1870 and P . aberrans Waagen, 1875 from the Callovian of Kutch, but the figures mentioned in the description did not correspond to the actual species. For P . spirorbis, the plate illustrated the holotype of an entirely different species ( P . aberrans ). On the other hand, P . spirorbis was illustrated as the lectotype of P . aberrans . Later, Spath (1924) introduced a new genus, Subgrossouvria, based on Waagen's P . aberrans as type species. He also erected another genus, Indosphinctes, and included P . spirorbis Waagen, 1875 within the synonymy of I . indicus (Siemiradzki, 1899). Spath (1931) was aware of wrong numbering of plates of Waagen's two species. But subsequent workers were ignorant of these taxonomic errors and continued to refer Waagen's wrong plate numbers. We have here described both the type specimens and provided diagnoses for Spath's two genera. We plead for this taxonomic correction in the incoming revised Treatise on Jurassic ammonites.